Impacto del ruido de tráfico en la valoración económica de inmuebles aledaños a la extensión de la vía Simón Bolívar en el tramo Carapungo - Mitad del Mundo - Aguas Jaramillo, Carlos Andrés (2018)
The objective of this research is to analyze, simulate and assess the impact of traffic noise from the extension of the Simón Bolívar avenue (Carapungo - Mitad del Mundo section) in the sale and rental price of the properties adjacent to it. Within this framework, the research carried out was based on three fundamental points of execution: the survey and data collection, the simulation and analysis, and the final statistical evaluation of the results. In a first phase, activities related to the collection of pertinent study information were carried out. In this process, the geographical location, land disposition, specific factors of the dwelling as well as the vehicle flow count and the road classification were obtained. Consequently, a noise map was simulated using the CADNA-A acoustic simulation software, based on the collected road data, which reflects an estimated noise level value for each receiver, in order to subsequently relate their influence on the economic field. Finally, the analysis of results was formulated through multivariable linear regressions using the software R of statistical analysis, which results in a chart of coefficients where the percentage impact of each factor in the total price of the property is appreciated according to each neighbourhood, either for rent or sale. Thus, the influence of traffic noise could be quantified in an economic way in each of the houses or dwellings adjacent to the road analyzed.